Analisis Simpanan Mitra Berjangka (SI MIKA) Menurut Fatwa DSN MUI Nomor 115/DSN-MUI/IX/2017 - Dhona, Risma; Mubarok, Ahmad Fauzan; Nafisah, Zahrotun (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
This research found the suitability of the term savings product (Si Mika) at the Sharia Savings and Loans and Financing Cooperative (KSPPS) BMT Mitra Utama Jepara with the DSN MUI Fatwa Number 115/DSN-MUI/IX/2017. The method used is descriptive qualitative, with data collection through interviews, observation and dokumentation. The research result show that Si Mika products use the Wadiah contract, even though they should use the Mudharabah contract according to the applicable fatwa. There are discrepancies in practice, especially regarding transparency and understanding of contracts among employees and members. Many members do not understand the contracts and profit sharing calculations, and there are differences in understanding between the Sharia Supervisory Board (DPS) and management. This research recommends that KSPPS BMT Mitra Utama consider changing the Wadiah contract to a Mudharabah contract and improve communication and understanding of the product between all parties. It is hoped that these findings will provide insight for KSPPS managers in ensuring the conformity of their products with sharia principles and increase member trust.